AcrAB Efflux Pump Plays a Role in Decreased Susceptibility to Tigecycline in Morganella morganii - Ruzin, Alexey (American Society for Microbiology, 2005)
Transposon mutagenesis of a clinical isolate of Morganella morganii, G1492 (tigecycline MIC of 4 μg/ml), yielded two insertion knockout mutants for which tigecycline MICs were 0.03 μg/ml. Transposon insertions mapped to acrA, which is constitutively overexpressed in G1492, suggesting a role of the AcrAB efflux pump in decreased susceptibility to tigecycline in M. morganii.